BMI Trumps Age in Decision for Endometrial Biopsy: Cohort Study of Symptomatic Premenopausal Women. Issue 10 (October 2016) - Wise, Michelle R.; Gill, Premjit; Lensen, Sarah; Thompson, John M. D.; Farquhar, Cynthia M.
Abstract : (Abstracted from Am J Obstet Gynecol 2016; doi: 10.1016/j.ajog.2016.06.006) The most common reason for referral to a gynecologist is abnormal uterine bleeding (AUB). Heavy or irregular vaginal bleeding often leads to an invasive diagnostic test such as endometrial biopsy or hysteroscopy.